Impact of Technology on Language Learning: A study of Translation Apps and their Usage at Undergraduate Level in University Education (Journal of Social Sciences Review, 2024)
Translation apps have a helpful role in language learning, using the technology to present, re-enforce and assess material. These apps are tools to enable language acquisition across different contexts and have become indispensable in university education with the speed of technological advancement. Urlaub and Dessein (2022) indicated that machine and human translation systems are becoming increasingly prevalent in language education. Translation practices cannot omit these tools; we have computer-aided translation technologies and online dictionaries. The impact of translation apps on undergraduate translation students' achievement is investigated; samples were 100 respondents. Students understand the benefits of using translation apps, like improved language skills. Plus, it's much easier to learn than traditional ways, but obstacles prevent the most effective use of these translation apps. Key barriers are the cost of internet access, lack of proper training, and occasional confusion when using the apps. Despite these hurdles, most respondents said they were optimistic and had learned to read from translation apps, describing their utility for language learning. The findings imply that translation apps must be integrated into undergraduate education to facilitate language acquisition and translation skills. The further the potential of these technologies is maximized in academic settings, the greater the addressing of challenges such as those connected to internet costs and training.
Keywords: Translation Apps; Translation Errors; Translator Training; Language Improvement; Speaking and Writing Skills; Translation Competence; Translation Quality; Language